Comprehensive Credit Risk Management of Policy Export Credit Insurance Institutions - Liu, Ming; Zhu, Jie; Bian, Yuanchao; Chen, Liping (Journal of Accounting, Business and Finance Research, 2018)
In the context of the turbulent international political situation, the uneven development of social development and the stagnation of economic development in recent years, China’s promotion of foreign trade and economic transformation and upgrading and the “Belt and Road” strategy are necessary to pay more attention to the research and control of export credit risks, so policy exports is particularly urgent and important for credit insurance institutions to conduct research on credit risk control activities in support of the “going out” process of Chinese goods and capital. At the same time, unlike general commercial financial institutions, the starting point and foothold of credit risk management of policy financial institutions should be “maximizing social benefits” rather than the “maximum economic benefits” of traditional risk management theories. The target set of the risk management system of the export credit insurance institution is repositioned. Therefore, this paper attempts to sort out the research results of the existing policy-oriented export credit institutions, and from the perspective of comprehensive risk management, through the analysis of the characteristics and difficulties of the credit risk management of policy-oriented export credit insurance institutions, the company builds a comprehensive credit risk management system. The ideas and structure are discussed, and preliminary suggestions are put forward on the basis of this, in order to provide reference for the company to further improve the comprehensive risk management system.